Respons Dosis Biotip Rumput Belulang (Eleusine Indica L. Gaertn) Resisten-Glifosat Terhadap Glifosat, Parakuat Dan Indaziflam - Satria Parlindungan Dalimunthe; Edison Purba; Meiriani Meiriani (Jurnal Agroekoteknologi, 2015)
Goosegrass (Eleusine indica) is one of weeds commonly found in oil palm plantation of which isgetting more difficult to control with glyphosate during the last few years in Adolina Estate, PTPNIV. This research aims to determine the dose response and level of resistance of the glyfosatresistenpopulation to paraquat, glyphosate, and indaziflam. The rates of glyphosate applied were 0,60, 120, 240, 480, 960, 1920 g a.i. ha-1; paraquat at 0, 50, 100, 200, 400, 800, 1600 g a.i. ha-1 andindaziflam at 0, 12,5, 25, 50, 100, 200, 400 g a.i. ha-1. The treatments were arranged in randomisedblock design (RBD) and each treatment was made in three replicates. The results showed that theputative glyphosate-resistant population collected from Adolina Estate was resistant to glyphosateand paraquat is the survival of resistant-glyphosate was 100 % at 480 g a.i glyphosate/ha and 86,7% at 400 g a.i paraquat/ha. The level of resistance to glyphosate and paraquat were 7,5 and 5,5 foldof the susceptible population respectively. Meanwhile, indaziflam controlled satisfactorily thispopulationKeywords: Glyphosate, Paraquat, Indaziflam, Eleusine indica, Resistance